Real Time PCR and Urine Cytology for Detection of BK Human Polyoma virus in-patient with Hemorrhagic Cystitis in Iraq - Faiz Kamel Al-Salami (Journal of Global Pharma Technology, 2019)
Hemorrhagic cystitis (HC) is considering one of the important complications in lower UT. Hemorrhage, hematuria, and dysuria are most common symptoms. In hemorrhagic cystitis, short-term hematuria can also be seen in bladder infections a result of viral infection. Viral cystitis represents another form of non-bacterial urinary tract infection touching adult and children. Human polyoma virus BK types I and V, Adenovirus types 21 and 11 and CMV viruses also can be cause of hemorrhagic cystitis. For direct detection BK polyoma virus from the aim of the present study work was to find out the relation of polyoma virus BKVS with acute syndrome consists of hematuria. This study was performed on two hundred and thirty bloody urine and blood specimens were collected from patients group comprised 170 male and 60 female age group 6 -65 years Patient samples (Urine and blood) were collected for detection of Human polyoma virus (BKVS) by using urine cytology, Real time PCR and conventional PCR technique. All bloody urine cultured on ordinary media to differentiate between bacterial and viral infection. The result of present study was found that 154 samples (67%) have positive bacterial culture which excluded and the other 76 samples(33%) give negative bacterial culture were included as suspected a viral cause of hematuria. All negative culture cases was classified as 4(5.26%) patients with glomerulonephritis, 15 (19.73%) chronic renal failure, 14 (18.42%). urinary tract infection, 27(35.5%) kidney transplantation 16 (21.5%) cystitis. urine cytology for detected decony cell (DC) showed that 13(17.1%) samples were positive for BKVS and 87(82.9%) were negative. All urine patients 76 with 25 urines samples of control were analyzed by RT-PCR for detection BVS. It was found only 5(6.67%) as a positive result. In conclusion this study report the design, development and application of real time PCR and urine cytology assay for rapid, specific and highly sensitive detection of BK virus genotype I2b.Keywords: Real Time PCR, Urine cytology, BK virus& Haemorrhagic cystitis.